1995
DOI: 10.1021/ja00123a008
|View full text |Cite
|
Sign up to set email alerts
|

The Manganese-Containing Polyoxometalate, [WZnMnII2(ZnW9O34)2]12-, as a Remarkably Effective Catalyst for Hydrogen Peroxide Mediated Oxidations

Abstract: The disubstituted manganese polyoxometalate, [WZ1Mn2(ZnW9034)2]'~-, has been used as a catalyst for the epoxidation of alkenes and the oxidation of secondary alcohols to ketones in biphasic (water-organic) reaction media using hydrogen peroxide (30% aqueous H 2 0 2 ) as the oxygen donor. At subambient temperatures, epoxidations are highly selective with little dismutation of hydrogen peroxide by homolysis or formation of side products by allylic oxidation. Thus, cyclohexene was oxidized to cyclohexene oxide at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(88 citation statements)
references
References 1 publication
4
83
0
1
Order By: Relevance
“…However, the catalytic reactivity of such a metalloporphyrin-POM assembly has yet to be examined. 10 We report herein formation of a 2:1 complex between a nonplanar Mo(V)-porphyrin, ( …”
Section: [Mo(dpp)(o)(h 2 O)]mentioning
confidence: 97%
See 1 more Smart Citation
“…However, the catalytic reactivity of such a metalloporphyrin-POM assembly has yet to be examined. 10 We report herein formation of a 2:1 complex between a nonplanar Mo(V)-porphyrin, ( …”
Section: [Mo(dpp)(o)(h 2 O)]mentioning
confidence: 97%
“…Polyoxometalates and heteropolyoxometalates (POMs) are widely known as functional materials in catalytic oxidation 25 reactions, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] metallorganic-POM hybrid catalysts. 9 In particular, the facile incorporation of transition-metals into lacunary-type POMs has attracted significant interest for preparation of oxidation catalysts with high activity.…”
Section: Introductionmentioning
confidence: 99%
“…4, 13 We have shown that in the microwave-assisted reactions there is no need for the preparation of such ammonium salts, and they could be successfully substituted with commercially available TBAHS. However, the test of other common PTC catalysts showed that, like under conventional conditions, the oxidation reactions occur most efficiently in the presence of hydrogen sulfate ions probably because of their sufficient acidity.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] However, much of these methods involve the use of expensive reagents, harsh reaction conditions, and leading to the generation of a large amount of toxic waste. 17,18 Because of these facts, there is still a need to develop new environmentally benign routes that meet industrial demands for this transformation.…”
Section: Introductionmentioning
confidence: 99%